The Effect of Lower Extremity Internal and External Rotation on the Hindfoot Alignment Moment Arm and Hindfoot Alignment Angle. Issue 4 (22nd October 2020) - Okroj, Kamil; Rogero, Ryan G.; Corr, Daniel; Fuchs, Daniel J.; Winters, Brian S.; O'Neil, Joseph T.; Shakked, Rachel J.; Raikin, Steven M.
Category: Ankle; Hindfoot Introduction/Purpose: The hindfoot moment arm was first described by Saltzman and el-Khoury to evaluate hindfoot varus and valgus alignment and has been well described and validated in the literature. It is commonly used by surgeons for preoperative planning of various hindfoot reconstructive procedures. The hindfoot alignment angle (the angle formed by the intersection between the tibial axis and the calcaneal axis) is another metric of measuring hindfoot alignment commonly utilized by surgeons. The purpose of this study was to determine if rotation of the hindfoot alters the hindfoot alignment moment arm and hindfoot alignment angle. We hypothesize that slight changes in internal and external rotation of the foot during x-ray positioning will have a large effect on the hindfoot moment arm and hindfoot alignment angle. Methods: We prospectively enrolled 29 patients, totaling 58 lower extremities, presenting to outpatient clinic for evaluation of a foot and ankle complaint. Patients <18 years of age, unable to perform bilateral weightbearing radiographs, or presenting for postoperative visits from recent foot and ankle surgery were excluded. Bilateral Saltzman hindfoot radiographs in neutral, 10 degrees of internal rotation, and 10 degrees of external rotation were performed. Marking lines were drawn on the standing platform to standardize rotation, with patients aligning their second ray with the lines. A fellowship-trained foot and ankle orthopaedic surgeon and an orthopaedic surgery resident individually measured the hindfoot moment arms and alignment angles. Analysis of variance (ANOVA) testing was used to assess for differences in hindfoot moment arm and hindfoot alignment angle in neutral, internal, and external rotation. Intra- and inter-observer agreement (95% limits) and intra-class correlation coefficients were calculated to assess for intra- and inter-observer reliability. Results: The cohort consisted of 11 (37.9%) males and 18 (62.1%) females, with a mean age of 48.7 (SD=14.7) years and mean body mass index (BMI) of 29.9 (SD=6.6) kg/m2. The mean hindfoot moment arms were 4.6 (SD=6.7) mm, 11.3 (SD=3.4) mm, and -5.4 (SD=6.2) mm in neutral, internal, and external rotation, respectively. The mean hindfoot alignment angles were 4.5 (SD=5.6) degrees, 18.6 (SD=6.8) degrees, and -10.9 (SD=10.6) degrees in neutral, internal, and external rotation, respectively. There was a significant difference in both the hindfoot moment arm (p<0.001) and hindfoot alignment angle (p<0.001) among rotational positions. A strong positive correlation existed between the amount of rotation and both moment arm (r=0.78; p<0.001) and alignment angle (r=0.84; p<0.001). Conclusion: There appears to be significant variability in both the hindfoot moment arm and hindfoot alignment angle with respect to rotation of the patient's lower extremity. Orthopaedic surgeons should carefully scrutinize limb rotation when making clinical decisions based on the hindfoot moment arm or alignment angle.